Ojciec jako organizator czasu wolnego - Gębka, Mikołaj (Wydawnictwo Naukowe UAM, 2008)
The article shows that the role of the free time organiser is such a role of the father that, paradoxically, is both existent and (virtually) non-existent, depending on which aspect of the social role of the father is considered. The role does exist in the sense that it is actually realised by fathers. However, it requires that it be discovered by fathers themselves, including all its importance, which is where it almost ceases to exist, as the importance is marginalised in fathers' awareness.
The father as the free time organiser